'Except that Joss Whedon is god': fannish attitudes to statements of author/ity. (July 2016) - Fathallah, Judith
Early internet and fan studies theorists believed the New Media context and work of the active fan would bring theories like the Death of the Author to fruition. Contemporary fan studies scholars are more reserved, acknowledging diversity in fan attitudes. Through analysis of a LiveJournal article with comments on authors' views concerning fanfiction, this article demonstrates the paradoxical investment in various forms of authorial authority espoused across fan communities, as well as defiance and repudiation of them. I argue that while the authors quoted are denied legitimate authority through various tactics, the concept of an originating, proprietary authorship, with attendant capitalist powers and rights, retains much influence. The concept of the author holds more power than the individual figures attempting to wield it, and fans attribute or deny the power of authorship to particular figures according to their public personas and cultural politics. In this sense, fans may withhold or bestow legitimation through the operation of Foucault's author-function, interpreting text and statements of authority through the public persona of the author.